Growth phase variation of integration host factor level in Escherichia coli. - Ditto, M D (1994)
We have measured the intracellular abundance of integration host factor (IHF), a site-specific, heterodimeric DNA-binding protein, in exponential- and stationary-phase cultures of Escherichia coli K-12. Western immunoblot analysis showed that cultures that had been growing exponentially for several generations contained 0.5 to 1.0 ng of IHF subunits per microgram of total protein and that this increased to 5 to 6 ng/microgram in late-stationary-phase cultures. IHF is about one-third to one-half as abundant in exponentially growing cells as HU, a structurally related protein that binds DNA with little or no site specificity. Wild-type IHF is metabolically stable, but deletion mutations that eliminated one subunit reduced the abundance of the other when cells enter stationary phase. We attribute this reduction to the loss of stabilizing interactions between subunits. A mutation that inactivates IHF function but not subunit interaction increased IHF abundance, consistent with results of previous work showing that IHF synthesis is negatively autoregulated. We estimate that steady-state exponential-phase cultures contain about 8,500 to 17,000 IHF dimers per cell, a surprisingly large number for a site-specific DNA-binding protein with a limited number of specific sites. Nevertheless, small reductions in IHF abundance had significant effects on several IHF-dependent functions, suggesting that the wild-type exponential phase level is not in large excess of the minimum required for occupancy of physiologically important IHF-binding sites.